SYNTHESIS OF NANO ZIRCONIUM OXIDE AND THE EFFECT OF ITS ADDITION ON POLYMETHYL METHACRYLATE AS BONE CEMENT - Fauzan, Raihan
Nearly 20% of Indonesia's population suffers from osteoporosis so that they are prone to fractures in the spine and 25% of them die. One of the treatment efforts is vertebroplasty or injection of PMMA (Polymethyl Methacrylate) bone cement into the spine. However, due to its low radiopacity, PMMA requires radiopaque fillers and one of the most commonly used is Zirconium oxide because it is known to improve the mechanical properties of PMMA. In this research, nano Zirconium oxide was synthesized using the sol gel method. Parameters that were varied were pH 6, 9, and 11, and calcination temperature 700 oC and 1000 oC. The addition of oleic acid is also carried out which is assumed to prevent agglomeration. The results showed that pH 11 produced the most ZrO2 with a yield of 94.48%. A temperature of 1000 oC produces ZrO2 with a larger and more crystalline crystallite size. There is still agglomeration so that the addition of oleic acid cannot be said to be effective. Furthermore, variations of pH 11 and temperature of 1000 oC were selected to be included in PMMA because the particle size was the smallest. The addition of ZrO2 succeeded in increasing the radiopacity of PMMA, but decreased its tensile strength due to the uneven distribution of particles. The presence of ZrO2 also reduces the hydrophilicity of PMMA, thereby reducing the water absorption ability.